Análise da viabilidade de implantação de medidas de redução e reuso de água: estudo de caso da construção de um edifício residencial - Kataoka, Danilo [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The increasing imbalance between supply and demand of water resources has generated a growing concern in the population, in order to encourage studies on the applications of measures that help their management, in order to guarantee water for future generations. The present work presents a study for the use of rainwater, water reuse and applications of water devices in an apartment building, in the municipality of Mauá (SP). The water abstracted will be used for non-potable use, such as discharges in toilets, floor cleaning and garden watering. For the study, improvement and need for water conservation in the construction industry, both during the construction period and also, and especially, throughout the useful life of the buildings. The research was carried out, characteristics of the studied building and parameters for spending of expenditures and consumption related to the use of water. Afterwards, the proposal for the rational use of water without building is started, with the implementation of a water reaction system, rainwater harvesting system and water reduction devices. Through estimates of the water savings generated and preliminary budgets for the implementation of the proposed measures, the period of return on investment was calculated. For a studied building, the reducing devices provide significant savings and have a faster return period than the greywater reuse system. Although the reuse provides less demand for drinking water in the building, the investment required for its implementation is high. In addition, by applying only reducing devices, it is estimated that average internal consumption per apartment would be within the range of minimum monthly water tariffs charged by the supply network. Rainwater use has proven to be useful, but it is quite useful for external demands and has a considerable payback period

O crescente desequilíbrio entre oferta e demanda dos recursos hídricos tem gerado uma preocupação crescente na população, de maneira a incentivar estudos a respeito de aplicações de medidas que auxiliem a gestão dos mesmos, de forma a garantir água para as gerações futuras. O presente trabalho apresenta um estudo para o aproveitamento da água de chuva, reuso de águas cinzas e aplicação de dispositivos economizadores de água em um edifício de apartamentos, no município de Mauá (SP). A água captada será destinada ao uso não potável, como descargas em vasos sanitários, limpezas de pisos e regas de jardins. Para o estudo, primeiramente realizou-se uma revisão bibliográfica do assunto de maneira a integrar informações a respeito do uso, desperdício e necessidade da conservação de água na construção civil, tanto ao longo do período de obras como também, e principalmente, ao longo da vida útil das edificações. Realizada a pesquisa, foram levantadas características do edifício estudado e parâmetros para estimativas de gastos e consumos relativos ao uso de água. Em seguida, deu-se início à proposta de uso racional de água no prédio, com implantação de um sistema de reuso de águas cinzas, sistema de captação de águas pluviais e de dispositivos redutores de água. Através de estimativas da economia de água gerada e orçamentos preliminares para a implantação das medidas propostas, calculou-se o período de retorno do investimento. Para a edificação estudada, os dispositivos redutores proporcionaram uma economia significativa e apresentaram um período de retorno mais rápido em relação ao sistema de reuso de águas cinzas. Apesar do reuso proporcionar menor demanda de água potável na edificação, o investimento necessário para a sua implantação é alto. Além disso, aplicando-se apenas dispositivos redutores, ... (Resumo completo, clicar acesso eletrônico abaixo)
Analysis of the feasibility of implementing water reduction and reuse measures: case study of the construction of a residential building
Keywords: Aguas pluviais; Eficiência do uso da água; Águas cinzentas (Resíduos de águas domésticas); Edificações; Rain-water (Water-supply)